(untitled) (Contemporary Mathematics, 2021)
We study permutation polynomials through the device of the polypermutation group of an associative ring R, denoted by Pgr(R). We derive some basic properties and compute the cardinality of Pgr(Z/pk ) when p ≥ k. We use this computation to determine the structure of Pgr(Z/p2 ).